Pengaruh Inflasi, Suku Bunga, dan Nilai Tukar terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2014-2023 - Khoirani, Annisa; Dini Fitrianti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of inflation, interest rates, and exchange rates on the Jakarta Composite Index (JCI) for the 2014-2023 period. The sampling technique used in this study was purposive sampling, with 120 samples taken over a 10-year observation period. The data used are secondary data in the form of time series data from historical monthly data reports published on the official website of Bank Indonesia and Yahoo Finance for the 2014-2023 period. The research method used is a quantitative method. The data analysis technique used is statistics and multiple linear regression analysis using SPSS version 25 and Microsoft Excel software. The results of this study, based on simultaneous tests, state that the variables of inflation, interest rates, and exchange rates have a simultaneous effect on the Jakarta Composite Index for the 2014-2023 period. Partial testing indicates that inflation has no effect on the Jakarta Composite Index (JCI) for the 2014-2023 period, interest rates have a negative effect on the Jakarta Composite Index (JCI), and exchange rates have a positive effect on the Jakarta Composite Index (JCI).